Emerging bisphenol a replacements (colour developers) in indoor dust from Spain - María Jesús Dueñas-Mas; Ana Ballesteros-Gómez; Soledad Rubio (Emerging Contaminants, 2019)
Bisphenol A (BPA) and replacements, such as bisphenol S (BPS) and F (BPF) and other substitutes (BPS-MAE, D-8 and TGSA) have been recently reported in thermal paper. In this study, BPA, BPS, BPF; BPS-MAE, D-8 and TGSA were analysed in indoor dust collected in Spain from different microenvironments (living rooms, bedrooms, cars and offices). Levels were compared with those reported in our previous study (shops and other public microenvironments, where frequent use of thermal paper is expected). We investigated the differences between microenvironments, possible correlations between compounds and estimated the ingestion rates. BPS-MAE, D-8 and TGSA were present at levels up to 529, 128 and 356 ng g−1, respectively, in all the microenvironments. The highest levels were measured in cars. Keywords: Bisphenol A, Bisphenol F, Bisphenol S, BPS-MAE, D-8, TGSA, Indoor dust